Warnock 40 Years On: The Development of Special Educational Needs Since the Warnock Report and Implications for the Future - Lindsay, Geoff; Dockrell, Julie; Wedell, Klaus (Frontiers Media SA, 2020)
2018 marked the 40th anniversary of the landmark Warnock Report in England on special educational needs (SEN). In recognition of this anniversary we called for submissions to a new Research Topic, Warnock 40 Years On. This Research Topic is dedicated to Baroness Mary Warnock who chaired the UK government's committee whose seminal report in 1978 bears her name, and whose death was announced on 20th March 2019, as the Research Topic was being completed. Although there had been reports on some disabilities before then, the Warnock Report was the result of the first comprehensive review of the whole range of children with special educational needs. Despite its subtitle echoing previous history, namely Report of the Committee of Enquiry into the Education of Handicapped Children and Young People, its main title proposed a new dawn: Special Educational Needs. Chaired by Mary Warnock, the Committee produced a review and made a wide range of recommendations that were truly ground breaking. This was not just about terminology. Rather, the Warnock Report was responsible for changing the conceptualisation and legislative framework in England, and the Education Act 1981 that followed the report had a totally new system for assessment and determining provision. Also, the Warnock Report recommended elements that in many countries we now take for granted - but at that time were highly original. For example, the meaningful engagement of parents, including their being central partners in the assessment of SEN and in making decisions on the appropriate needs, including SEN, of individual children and young people: a greatly updated process of assessment; the inclusion of a chapter on children under five years; the role of special schools; the curriculum; the transition from school to adult life; teacher education; the roles of professionals; the health and social services and voluntary organisations; and last but not least - research. The impact of the Warnock Report 1978 for England in particular was substantial. Impact has also been seen internationally, as professional practice and state legislation have developed, not least the policy development towards integration, or as we now generally refer, inclusion. We produed this Research Topic to celebrate this 40th anniversary of the Warnock Report.